Subjective uncertainty, expectations, and firm behavior - Stefan Lautenbacher (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2021)
Based on a new survey question in a large and representative panel of German firms, this paper introduces a novel measure of managers' subjective uncertainty. I compare this measure of business uncertainty to respondents' business expectations and document a strong negative relationship. However, the link is much weaker in bad times, since uncertainty is then persistently high - even when expectations are favorable. I continue by investigating the relative importance of uncertainty and expectations for corporate decisions. Exploiting information on firms' investment and labor reactions to the COVID-19 crisis, I do not find evidence that uncertainty induced "wait and see" behavior. However, a deterioration in managers' expectations and in their assessment of their firms' business situation predicts investment deferral and a reduction in employment.
Keywords: C83; D22; D84; E32; E71; 330; subjective uncertainty; expectations; firms; survey data; corporatedecisions; business cycles